Mechanical analysis of 3D printed dental restorations manufactured using different resins and validation with FEM analysis - Buse Cebi Gul; Fatih Demirci; Nagehan Baki; Erkan Bahce; Mutlu Özcan (BMC Oral Health)
Abstract Purpose The aim of this study was to compare the wear and fracture resistance of single crowns produced from newly developed 3D printer resins used to produce permanent crowns and currently used composite CAD/CAM discs, after being thermomechanically aged in a chewing simulator. Materials and methods A total of 112 stainless steel die models simulating mandibular left first molars were produced, 8 for each group. Single crowns were produced from 3 different discs (Grandio Voco [GR], breCAM HIPC [HC], and Shofu HC [SF]) by CAD/CAM milling method and manufactured from from 4 different permanent composite resins (Nexdent C&B MFH [ND], Permanent Bridge Saremco [PB], VarseoSmile Crownplus [VSC], and Şenertek P-Crown [PC]) using the 3D printing method. Stereomicroscopy, scanning electron microscope (SEM) and Finite Element Method (FEM) analysis was performed. Data were analyzed using ANOVA, paired-t tests and Tukey’s HSD test (alpha = 0.05). Results As a result of thermomechanical aging, significant difference was found between the groups in wear and fracture resistance (P < .05). The highest wear resistance was found in the VSC group, and the lowest wear resistance in the PC group. As a result of the compression test, the highest fracture resistance was noted in the GR group and the lowest in the PC group. FEM analysis performed to validate fracture experiments showed an 87% similarity to the in-vitro data. Conclusions The crowns in all groups produced by CAD/CAM milling and 3D printing provided acceptable in vitro wear and fracture resistance for clinical application. The wear and fracture resistance of resin-based materials should be supported by clinical studies.